The Portrayal of Class Struggle in Money Heist - Jeremy Kayne Valiant; Setefanus Suprajitno (Institute of Research and Community Outreach - Petra Christian University, 2026)
ABSTRACT This study explores the portrayal of class struggle in Money Heist (2017) using Karl Marx’s (1848/1969) theory on class struggle. This study analyzes the series using a qualitative approach to uncover how the characters' backgrounds and actions reflect structural inequality within capitalist society. Key findings show that the characters experience precarity, exclusion, and lack of recognition that shape their struggles and decisions. The act of printing money at the Royal Mint is presented as a form of resistance against the state’s monopoly over value creation. The study also found collective resistance forming through the exposure of state violence and manipulation. This study concludes that Money Heist functions as a critique of capitalism, showing how marginalization can produce resistance under oppressive systems. This study concludes that Money Heist functions as a critique of capitalism, showing how marginalization can produce resistance under oppressive systems.